Targeting miRNA‐1a and miRNA‐15b: A Novel Combinatorial Strategy to Drive Adult Cardiac Regeneration - Ting Yuan; Meiqian Wu; Chaonan Zhu; Hao Yu; Minh Duc Pham; Katharina Bottermann; Yijie Mao; Yue Wang; Mathias Langner; Mirko Peitzsch; Arka Provo Das; Silke Kauferstein; et al. (Advanced Science)
Abstract Despite its promise, cardiac regenerative therapy remains clinically elusive due to the difficulty of spatio‐temporal control of proliferative induction, and the need to coordinately reprogram multiple regulatory pathways to overcome the strict post‐mitotic state of human adult cardiomyocytes. To address this unmet therapeutic need, a combinatorial miRNA interference screen is performed specifically targeting cardiac‐predominant miRNAs regulating key aspects of cardiomyocyte mitotic induction to cell‐cycle completion in neonatal rat cardiomyocytes. In doing so combinatorial interference of miRNA‐1a and miRNA‐15b (LNA‐1a/15b) is identified as drivers of adult cardiomyocyte proliferation. Due to miRNA‐1a/15b function on multiple processes modulating adult cardiomyocyte mitosis, its inhibition augmented adult cardiomyocyte cell‐cycle completion and daughter cell formation, and improved contractility in 3D human cardiac organoids, and in a mouse model of ST‐segment elevation myocardial infarction. Due to the cardiac‐restricted pattern of miRNA‐1a/15b expression, this strategy provides a feasible means for specific cardiomyocyte proliferative induction with minimal risk of neoplasm formation and off‐target toxicity. The approach further highlights an underutilized therapeutic strategy for simultaneous co‐regulation of multiple disease pathways through combinatorial interference of miRNAs.